Mobility Analysis of Kinematic Chains - Dargar, Ashok; Hasan, Ali; Khan, RA (Kathmandu University Journal of Science, Engineering and Technology, 2010)
In the present work a simple and efficient method is proposed to identify whether a kinematicchain posses total, partial or fractionated mobility. The proposed method uses the chain flowvalues (CFV) derived from the flow matrix of the given kinematic chain and successfullyapplied to all known cases of 2 and 3 degree of freedom planar kinematic chains. Since themethod is systematic and efficient, it can be applied to the more complex chains which nothave been reported in the literature yet. This study will be helpful in dividing the frame andinput links from the view point of mobility. Some examples are provided to demonstrate theeffectiveness of this method.Keywords: Degree of freedom (DOF); Contour; Chain flow value (CFV).DOI: 10.3126/kuset.v6i1.3307Kathmandu University Journal of Science, Engineering and Technology Vol.6(1) 2010, pp25-32